Allium macrostemon Saponin Inhibits Activation of Platelet via the CD40 Signaling Pathway - Ling, Sisi; Jin, Lijun; Li, Shizheng; Zhang, Fangcheng; Xu, Qiong; Liu, Mingke; Chen, Xuke; Liu, Xiaolin; Gu, Jielei; Liu, Shiming; Liu, Ningning; Ou, Wenchao (Frontiers in Pharmacology, 2021)
Allium macrostemon saponin is a traditional Chinese medicine that exhibits anti-atherosclerosis effects. However, the mechanism of its action has not been fully clarified. Platelet activation induced by CD40L plays an important role in the process of atherosis. In the present study, we demonstrate for the first time that Allium macrostemon saponin inhibits platelet activation induced by CD40L. Moreover, the effects of saponin on platelet activation were achieved by activation of the classical CD40L-associated pathway, including the PI3K/Akt, MAPK and NF-κB proteins. In addition, the present study further demonstrated that saponin exhibited an effect on the TRAF2-mediated ubiquitination degradation, which contributed to the inhibition of the CD40 pathway and its downstream members. The findings determine that Allium macrostemen saponin inhibits activation of platelets via activation of downstream proteins of the CD40 pathway. This in turn affected TRAF2-associated ubiquitination degradation and caused an anti-thrombotic effect.